Desk Jockey: A Device to Increase Non-Exercise Activity Thermogenesis in Adults. Issue 1 (9th June 2020) - Tang, Jiangqi; Yeh, Yulyu; Scarchilli, Michael; Jen, K.-L. Catherine
Increased sedentary behavior (SB) has been shown to raise the risk of obesity and chronic diseases due to extended period of time spent sitting. This study aimed to investigate the effect of a portable device, "Desk Jockey" (DJ), on increasing non-exercise activity thermogenesis (NEAT) and reducing sedentary behavior in a simulated office environment. Thirteen participants whose daily work required long hours sitting were recruited and completed the study (seven males and six females). Metabolic rates (METs), energy expenditure (EE), respiratory quotient (RQ) and heart rates (HRs) were measured using an indirect calorimeter during five sessions. These included one sedentary and four sessions with different pedaling frequencies and resistances. Each session included a 10 min baseline, 20 min pedaling and 20 min post-pedaling/recovery periods. Ratings of DJ's usefulness were also obtained from each participants. Data revealed that METs, EE and HRs increased significantly (p's < 0.0001) during pedaling period compared to the baseline period even though METs were still low (2.5 ± 0.6 MET) in each session. Total EE was significantly higher in sessions with pedaling (p's < 0.0001) as compared with total sedentary session. RQ was not affected by pedaling. In high frequency sessions the METs during the 10 minutes recovery period were still higher (p's < 0.05) than those at baseline. Thus pedaling frequency was a more important factor to METs and EE than resistance. DJ was tolerated well and no adverse effects was reported. It can be used by office workers to increase METs and EE during and post pedaling periods without interfering with work.